Measurement of polychlorinated biphenyls (PCBs) in the soil samples of Taleghan region and investigation of the presence of biological agents capable of removing PCBs - Alireza Zakeri; Nastaran Akbarian; Kamand Hedayat (علوم محیطی)
Introduction: In the recent decades with the increase of population and the expansion of industries, various chemicals have entered the environment and polluted the ecosystem and PCBs are one of these life threatening contaminants. Microbial degradation of PCBs has been considered as one of the cost effective and efficient methods to the remove these contaminants from the environment.The aim of the present study was to measure the concentration of poly- chlorobiphenyls (PCBs) in the soil around power transformers in Taleghan region of Karaj. We also aimed to identify and extract bacteria that degrade PCBs to be used as biological removal in the environment.Material and methods: For this purpose, soil samplings were done at five stations in different places around power transformers. Samplings were performed in a depth of 20 cm in sterile conditions and samples were kept in glass containers. LB broth Blood Agar and McConkey culture media were used to identify and determine the bacteria degrading PCBs.Results and discussion: Five samples were examined, only two of which were positive for PCBs contamination. Microbial exploration was performed in these two samples. In one of the samples, the amount of PCBs was 3 PPM, while in the second sample, the total amount of PCBs was estimated to be less than 0.02 PPM. These two samples were cultured both directly and diluted. In samples 1 and 2, which were cultured directly, gram-negative bacilli grew. In diluted sample 1, no bacteria grew, while in diluted sample 2, cocci were grown and in gram coloring, it turned purple so it was gram-positive. Direct samples 1 and 2 contained bacilli and turned red (gram-negative) in response to gram coloring.Conclusion: The use of these bacteria to remove the compounds of PCBs is one of the useful ways to reduce pollution in these places, with the least harmful effects on the environment and at the same time the most profitable sectors of the industry.